Thunderclap Headache: A Primary Symptom of a Steroid-Responsive Encephalopathy with Autoimmune Thyroiditis - Naman Zala; Lena Wirth; Berit Jordan; Hagen Meredig; Timolaos Rizos (Case Reports in Neurological Medicine)
Thunderclap headache is frequently associated with serious intracranial vascular disorders and a usual reason for emergency department admissions. Association of thunderclap headaches with autoimmune disorders, such as steroid-responsive encephalopathy with autoimmune thyroiditis (SREAT), is highly unusual. Here, we report a patient who presented with high-intensity headache of abrupt onset. Cerebrospinal fluid (CSF) analysis revealed moderate lymphocytic pleocytosis without evidence of infectious, neoplastic, or metabolic causes. Brain magnetic resonance imaging showed no specific pathologies, and examinations for neuronal antibodies in serum and CSF were negative. The medical history revealed that seven years before, an episode of an aseptic meningoencephalitis with remarkable response to steroids was present. Finally, increased levels of serum anti-TPO antibodies were identified, and against the background of a previous steroid-responsive aseptic meningoencephalitis, diagnosis of SREAT was highly probable. Methylprednisolone therapy was initiated, and the patient recovered completely. In particular, because most SREAT patients respond very well to steroids, this case underlines the importance of taking SREAT into consideration during the assessment of a high-intensity headache of abrupt onset.